The frequency of the fear of crime - Farrall, Stephen (The British journal of criminology, 2004)
Research exploring the emotional responses to crime experienced by the citizens of several major European and North American countries, including the UK, has suggested that a significant proportion of the residents of these countries fear' crime. However, few researchers have explored the frequency with which citizens feel fearful. This brief research note reports on a study that explored the frequency and intensity of such feelings. The research suggests that few people fear crime frequently